THE PEOPLE PEDAGOGICALLY EDUCATE YOUTH PATRIOTISM AND TRADITIONALLY - Orazimbetov Yermekbay Keulimjaevich (Web of Journals Publishing, 2023)
In this article, examples of Karakalpak folk pedagogy are reflected in the traditions of patriotic education of young people based on the heroism of our ancestors in their struggle against external enemies.
Keywords: Karakalpak folk pedagogy, patriotism, history, Sak-massagats, Tumaris, Shiroq, heritage of ancestors.